2005
DOI: 10.1523/jneurosci.1193-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Activates Orexin/Hypocretin Neurons through the Cholecystokinin A Receptor

Abstract: Orexin A and B are neuropeptides implicated in the regulation of sleep/wakefulness and energy homeostasis. The regulatory mechanism of the activity of orexin neurons is not precisely understood. Using transgenic mice in which orexin neurons specifically express yellow cameleon 2.1, we screened for factors that affect the activity of orexin neurons (a total of 21 peptides and six other factors were examined) and found that a sulfated octapeptide form of cholecystokinin (CCK-8S), neurotensin, oxytocin, and vasop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 53 publications
6
79
0
Order By: Relevance
“…4 C and D). Moreover, we found that effects of other inhibitory or excitatory neurotransmitters, 5-hydroxytryptamine (5-HT) (19) or cholecystokinin (CCK) (20) were also decreased (Fig. 4 E and F).…”
Section: Elimination Of Gabab Receptors On Orexin Neurons Results In Anmentioning
confidence: 93%
“…4 C and D). Moreover, we found that effects of other inhibitory or excitatory neurotransmitters, 5-hydroxytryptamine (5-HT) (19) or cholecystokinin (CCK) (20) were also decreased (Fig. 4 E and F).…”
Section: Elimination Of Gabab Receptors On Orexin Neurons Results In Anmentioning
confidence: 93%
“…However, there is a difference in the source of calcium mobilization between the AVPinduced and the CCK-8S-induced responses. The CCK-8S-induced increase in [Ca 2ϩ ] i was not inhibited by thapsigargin ( Tsujino et al, 2005). In contrast, the AVP-induced response was sensitive to both thapsigargin and xestospongin C. The AVPinduced increase in [Ca 2ϩ ] i was inhibited ϳ50% of control value by these compounds.…”
Section: Discussionmentioning
confidence: 97%
“…Orexin neurons receive abundant inputs from the limbic system, the raphe nucleus, and the basal forebrain Yoshida et al, 2006). Intracellular calcium in orexin neu-rons is altered by a number of neuroactive substances, including cholecystokinin, neurotensin, AVP, oxytocin, neuropeptide Y (NPY), adenosine, serotonin, and noradrenaline (Fu et al, 2004;Tsujino et al, 2005;Yamanaka et al, 2006;Liu and Gao, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of phospholipase C by the ␤␥ subunit of the G-protein might be involved because OX2R is believed to couple with the Gq and Gi types of G-proteins (Zhu et al, 2003). We previously showed that orexin neurons are activated by CCK and AVP via the G-protein-coupled receptors (Gq), CCK A receptor, and the V1a receptor (Tsujino et al, 2005;Tsunematsu et al, 2008). Both CCK-and AVP-induced inward currents were robustly enhanced by removing the calcium ions from the extracellular solution.…”
Section: Discussionmentioning
confidence: 99%